Aplicação de autômatos sincronizáveis na segurança de sistemas a eventos discretos - Lucas Vinícius Ribeiro Alves (2020)
Manufacturing systems are increasingly subject to external attacks and failures, whether by defects in sensors and actuators or by communication problems. In this context, the security of these systems is an increasingly studied problem, including in the field of Discrete Event Systems (DES) using Supervisory Control Theory (SCT). In this work we propose to deal with security problems in DES using the Synchronizing Automata Theory, which allows us to use a synchronizing word to synchronize the supervisors and plants in case the state that the supervisor estimates the plant does not correspond to the physical state of the plant. The results of this work allow us to model systems and to extend the SCT to deal with models based in synchronizing automata, using the monolithic synthesis or applying local modular control, and to deal with complimentary techniques such as the supervisor reduction and supervisor localization. In addition, we propose a way to model systems that are not originally synchronizing as synchronizing automata inserting recovery events.